Project Based Learning: Model Pembelajaran untuk Meningkatkan Minat Belajar Tematik - Maya, Maya Agustina; Pipin, Tengku Hafinda; Wildatul Fajrina (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2024)
This quantitative study aims to measure the inscrease in interest Thematic learning for MIN 7 Aceh Barat students using the model Project based learning learning. The research population is fourth grade students, IV, V and VI MIN 7 Aceh Barat and research samples are all grade IV students of MIN 7 Aceh. Data is collected using a questionnaire. Data analysis using simple frequency formula. The results showed that interest in learning students experienced an increase after the application of the Project based learning. The results of the student learning interest questionnaire conducted before the implementation of the project-based learning model showed that only one student was included in the